Home Sanitation and Occupant Behavior: The Key to Reducing the Incidence of ARI in Toddlers - Andriyanto, Arif (Universitas Ibn Khaldun Bogor, 2025)
Acute respiratory infections (ARI) are a global public health problem, especially in developing countries, causing around 13 million deaths of children under five every year. In Indonesia, the incidence of ARI in children under five increased from 25% in 2013 to 47.17% in 2018. Factors such as the physical sanitation of the house and the behavior of residents, including ventilation, lighting, smoking habits and waste management, play a role in the incidence of ARI. Developing a stronger understanding of the importance of handling home sanitation and occupant behavior as the main key in reducing the incidence of ARI in children under five. The type of research used is a literature review. The study involved the analysis of national and international journals, with selection criteria focusing on indexing reputation, publisher, quality, content relevance, and data completeness. Based on the search and criteria testing, 13 articles were selected for review. Most of the studies used in the articles employed a cross-sectional design. The results from each article showed variations in the relationship between variables, but all found the occurrence of ARI. Household sanitation factors and occupant behavior play a significant role in the incidence of ARI in toddlers. Floor condition, wall condition, ventilation, lighting, humidity, and occupancy density affect the risk of ARI. Additionally, behaviors such as smoking indoors and using mosquito repellent coils increase the risk of ARI in toddlers.